GPR139 and Dopamine D2 Receptor Co-express in the Same Cells of the Brain and May Functionally Interact - Wang, Lien; Lee, Grace; Kuei, Chester; Yao, Xiang; Harrington, Anthony; Bonaventure, Pascal; Lovenberg, Timothy W.; Liu, Changlu (Frontiers in Neuroscience, 2019)
GPR139, a Gq-coupled receptor that is activated by the essential amino acids L-tryptophan and L-phenylalanine, is predominantly expressed in the brain and pituitary. The physiological function of GPR139 remains elusive despite the availability of pharmacological tool agonist compounds and knock-out mice. Whole tissue RNA sequencing data from human, mouse and rat tissues revealed that GPR139 and the dopamine D2 receptor (DRD2) exhibited some similarities in their distribution patterns in the brain and pituitary gland. To determine if there was true co-expression of these two receptors, we applied double in situ hybridization in mouse tissues using the RNAscope® technique. GPR139 and DRD2 mRNA co-localized in a majority of cells within part of the dopaminergic mesolimbic pathways (ventral tegmental area and olfactory tubercle), the nigrostriatal pathway (compact part of substantia nigra and caudate putamen) and also the tuberoinfundibular pathway (arcuate hypothalamic nucleus and anterior lobe of pituitary). Both receptors mRNA also co-localized in brain regions involved in responses to negative stimulus and stress, such as lateral habenula, lateral septum, interpeduncular nucleus and medial raphe nuclei. GPR139 mRNA expression was detected in the dentate gyrus and the pyramidal cell layer of the hippocampus as well as the paraventricular hypothalamic nucleus. The functional interaction between GPR139 and DRD2 was studied in vitro using a calcium mobilization assay in cells co-transfected with both receptors from several species (human, rat and mouse). The dopamine DRD2 agonist did not stimulate calcium response in cells expressing DRD2 alone consistent with the Gi signaling transduction pathway of this receptor. In cells co-transfected with DRD2 and GPR139 the DRD2 agonist was able to stimulate calcium response and its effect was blocked by either a DRD2 or a GPR139 antagonist supporting an in vitro interaction between GPR139 and DRD2. Taken together, these data showed that GPR139 and DRD2 are in position to functionally interact in native tissue.